Absence of ethnic differences in the pharmacokinetics of moxifloxacin, simvastatin, and meloxicam among three East Asian populations and Caucasians - Hasunuma, Tomoko; Tohkin, Masahiro; Kaniwa, Nahoko; Jang, In‐Jin; Yimin, Cui; Kaneko, Masaru; Saito, Yoshiro; Takeuchi, Masahiro; Watanabe, Hiroshi; Yamazoe, Yasushi; Uyama, Yoshiaki; Kawai, Shinichi (British journal of clinical pharmacology, 2016)
Aim To examine whether strict control of clinical trial conditions could reduce apparent differences of pharmacokinetic (PK) parameters among ethnic groups. Methods Open‐label, single dose PK studies of moxifloxacin, simvastatin and meloxicam were conducted in healthy male subjects from three East Asian populations (Japanese, Chinese and Koreans) and one Caucasian population as a control. These three drugs were selected because differences in PK parameters have been reported, even though the backgrounds of these East Asian populations are similar. Moxifloxacin (400 mg) was administered orally to 20 subjects, and plasma and urine levels of moxifloxacin and its metabolite (M2) were measured. Simvastatin (20 mg) was given to 40 subjects, and plasma levels of simvastatin and simvastatin acid were measured. Meloxicam (7.5 mg) was given to 30 subjects and its plasma concentration was determined. Intrinsic factors (polymorphism of UGT1A1 for moxifloxacin, SLCO1B1 for simvastatin, and CYP2C9 for meloxicam) were also examined. Results AUCinf values for moxifloxacin, simvastatin and meloxicam showed no significant differences among the East Asian groups. Cmax values of moxifloxacin and simvastatin, but not meloxicam, showed significant differences. There were no significant differences of data for M2 or simvastatin acid. Genetic analysis identified significant differences in the frequencies of relevant polymorphisms, but these differences did not affect the PK parameters observed. Conclusions Although there were some differences in PK parameters among the three East Asian groups, the present study performed under strictly controlled conditions did not reproduce the major ethnic differences observed in previous studies.